Establishment and Evaluation of a Stable Bovine Thyroid Cell Line for Investigating Foot-and-Mouth Disease Virus - Mao, Ruoqing; Sun, Dehui; Yang, Fan; Tian, Hong; Zhu, Zixiang; Zheng, Haixue; Liu, Xiangtao (Frontiers in Microbiology, 2018)
Foot-and-mouth disease virus (FMDV) has a wide host range. Its pathogenesis varies among hosts and types of viruses. Most investigations of pathogenesis have been performed on cattle and swine. However, FMDV research in cattle is hampered by the lack of a stable in vitro infection model. In this study, the stable bovine thyroid cell line hTERT-BTY from primary bovine thyroid (BTY) cells was established by telomerase reverse transcriptase over expression. The results of karyotype analysis and experiments on morphological and biological characteristics indicated that this cell line possessed the qualities of primary BTY cells, which could be extended indefinitely with stable morphology and steady growth rates. The hTERT-BTY cell line, has 60 chromosomes including 29 pairs of autosomes and 1 pair of sex chromosomes without structure aberrations. It can express thyroid-specific function genes thyroid-stimulating hormone receptor and sodium/iodide symporter in high abundance ratios. The cell line is sensitive to FMDV strains and is expected to be used as a powerful tool for FMDV clinical diagnosis, separation, detection and culture. Also, the different mRNA expression levels in infected and uninfected hTERT-BTY cells were analyzed in this study to identify the pathways of immunity using RNA-seq. The results suggested that the hTERT-BTY cell line could be regarded as an effective tool for the immune response exploration of FMDV. In conclusion, this study provided a useful tool for FMDV clinical diagnosis, separation, detection, and culture. The cell line also could serve as an in vitro model to study the mechanism underlying FMDV pathogenicity and host–virus interaction.